Filozofia egzytencjalna Alberta Camusa - Błaszczyk, Tomasz (Studia Europaea Gnesnensia, 2012)
The article presents the ideas of albert camus in the perspective of philosophy of existence. The task is to show, that the work of the writer can be interpreted as a valuable, deeply philosophical point of view on life.